Identification of Enterococcus faecalis by PCR in saliva of pediatric patients - Paula, Viviane Andrade Cancio de; Oliveira, Queila Braga; Brito, Ivana Ribeiro de Oliveira; Ferreira, Dennis de Carvalho; Cavalcante, Fernanda Sampaio; Teixeira, Lúcia M.; Santos, Kátia Regina Netto dos; Primo, Laura Guimarães Salignac (Archives of Oral Research, 2013)
Objective: This study aimed to identify E. faecalis in saliva of patients that were divided into two groups: 10 patients with caries lesions and 10 caries-free patients. Material and methods: Saliva samples were collected with a sterile swab and inoculated in enterococcosel media for 48 hours. The positive samples were subcultured in broth agar - blood medium for storage and subsequent PCR analysis. The data were analyzed using the SPSS (χ2). Results: From the 20 cases included in the study, 3 were positive in the Enterococcosel medium, and both tests (culture and PCR) used confirmed that three of them belonged to the species E. faecalis. No samples were positive in Enterococcosel broth in the group of caries-free patients. From the three samples that were identified as Enterococcus in broth (positive bile esculin test), an amplified for E. faecalis PCR analysis (p > 0.005). Conclusion: Through the use of PCR, it was possible to identify the genus Enterococcus and the species E. faecalis in saliva of patients with carious lesions – the pathogen that may influence the prognosis of diseases of the oral cavity.